Establishment of molecular breeding lines for aroma in rice / Yeap Hui Yin - Yeap, Hui Yin (2012)
Aroma is one of the most important traits of aromatic rice grain quality after grain appearance, amylose content, gelatinization temperature and kernel elongation. The genetic control and environmental variation of this trait are reported to be quite complex. To screen and select the F1 individuals with aroma, four molecular markers namely, EAP, ESP, INSP, and IFAP were used in this study together with sensory evaluation. The F1 individuals were obtained from different crosses between Malaysian local rice varieties (MR 219 and MRQ 50) with seven selected aromatic rice varieties from global popular aromatic rice cultivars and advance lines. The F1 seeds were planted together with their parents in the experimental field at the Institute of Biological Sciences, Faculty of Science, University of Malaya and examined for their agronomic performance in the year 2011. During molecular screening and sensory evaluation, homozygous aromatic F1 individuals were found to have better mean aroma score in leaf and grain compared to both heterozygous non-aromatic individuals and homozygous non-aromatic individuals due to crosses between two homozygous aromatic parents. However, some of the F1 with the absence of aroma alleles, produced aroma in both leaf and grain. Moreover, the aroma emitted from those F1 individuals was almost the same as the Pandan (Pandanus amaryllifolius) leaf aroma which has been linked to 2-acetyl-1-pyrroline (2AP). Thus, they were suspected follow BADH2 (betaine aldehyde dehydrogenase 2)-independent 2AP synthesis pathway. Genotypic and phenotypic analysis revealed that aroma in F1 individuals was successfully inherited in curve shaped seeds compared to non-curve shaped seeds. The yield performance was low in most of the F1 individuals, especially F1 from the crosses between aromatic and aromatic parents, except for F1 from MRQ 50/E 13. Among the F1 from 14 different crosses, F1 derived from MRQ 50/E 13 produced high yields and better aroma. In the present study, the integration of molecular markers and sensory methods were observed to be reliable and fast for screening the F1 derived from all crosses because these molecular markers distinguished homozygous aromatic, homozygous non-aromatic and heterozygous non-aromatic individuals whilst the sensory method evaluated the aroma emitted from leaf and grain during flowering to maturity stages.